The influence of non-product-related attributes on media brands' consumption - Linda Saulīte; Deniss Ščeulovs; Frantiések Pollák (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This paper outlines the importance and role of non-product-related brand attributes, e.g., user imagery and usage imagery, in local news media content consumption by a younger audience aged 15-24. Due to technological developments, new media content consumption patterns have emerged. New dynamic, interactive, and multiplatform marketplaces have changed how media brands deliver content and how audiences consume it. The main catalysts of change are multiple platforms, on-demand content consumption, and social media platforms. The increasing use of global social networks offers media brands possibilities to distribute content and connect with their audiences, all while creating new challenges and competition in local media. These changes have brought about possibilities of broadening media audiences, as well as challenges, e.g., because of decreasing media brand associations and preference being given to social media platforms and global media brands. Generation Z's traditional media consumption patterns are below average. This audience segment prefers mobile access and online media content on various platforms, uses social media more than other age range audiences, and chooses global media and social media platforms over national media brands. These dynamics increase the challenges for local news media brands in attracting and growing a future audience, as Generation Z consumes fewer national media content in their local or national language, and what they do consume is through the medium of social media. The authors analyse media consumption trends in Latvia and determine how media brands increase their equity and the consumption of media regarding younger audiences. This research was designed to understand media consumption trends via secondary information analyses and employs a quantitative survey to identify non-product-related brand attitudes. The research question of this paper is concerned with defining how media brand associations affect content consumption and engagement. We used regression analyses to predict the most significant correlations between brand attributes and content consumption and concentration. The study focuses on national news media brands.
Keywords: 650; consumer-based brand equity; media brand attributes; media branding; news media brands